Wavelet Transform Approach for Fault Detection of Three Phase Transmission Line Compensated with Series Capacitor - Sharma, Prachi; Ali, Shoyab; Kapoor, Gaurav (Asian Journal of Electrical Sciences, 2018)
This paper proposes fault detection technique for the protection of series capacitor compensated three phase transmission line using wavelet transform. Three phase series capacitor compensated transmission line is modeled and the proposed fault detection technique has been developed and tested using Simscape Power Systems toolbox of MATLAB software. Proposed scheme is tested by variations of parameters like fault type, fault resistance, ground resistance, fault location and fault inception time. The test results confirmed successful detection of fault.